2021
DOI: 10.3354/meps13607
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic pressures on reef-associated sharks in jurisdictions with and without directed shark fishing

Abstract: Shark populations have declined across the Caribbean region, with negative associations between shark abundance and human population density, open access to fishing, and proximity to large markets (‘market gravity’). This decline is frequently attributed to fishing mortality, which increases in areas closer to humans and outside marine reserves. Although it is difficult to disentangle the effects of fishing mortality from other anthropogenic pressures on sharks, comparing shark abundance and diversity in juris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 36 publications
1
15
1
Order By: Relevance
“…Large and old MPAs stood out as having a fairly higher nurse shark abundance than all other MPA categories, and similar or higher abundance than non-protected sites. These results are in apparent concordance with the findings of Bond and colleagues [ 52 ], who found Caribbean reef sharks ( Carcharhinus perezi ) to be more abundant in protected areas, and of Clementi [ 48 ], who also recorded a significantly higher CPUE of nurse sharks within protected areas than at fished sites in Belize. Bothe these studies focused on fairly large and old MPAs, and in concomitance with study further demonstrate the importance of area and time of enforcement for the positive effects of spatial protection to emerge [ 34 , 35 ].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Large and old MPAs stood out as having a fairly higher nurse shark abundance than all other MPA categories, and similar or higher abundance than non-protected sites. These results are in apparent concordance with the findings of Bond and colleagues [ 52 ], who found Caribbean reef sharks ( Carcharhinus perezi ) to be more abundant in protected areas, and of Clementi [ 48 ], who also recorded a significantly higher CPUE of nurse sharks within protected areas than at fished sites in Belize. Bothe these studies focused on fairly large and old MPAs, and in concomitance with study further demonstrate the importance of area and time of enforcement for the positive effects of spatial protection to emerge [ 34 , 35 ].…”
Section: Discussionsupporting
confidence: 91%
“…It is thus likely that the higher ER at LRA is a better indicator of local relative abundance than MaxN. MaxN at sites along the barrier reef of Belize was also found to be intermediate between LRA and GLO in a study by Clementi and colleagues [48], although the areas surveyed by the study differed from those explored here.…”
Section: Plos Onecontrasting
confidence: 51%
See 2 more Smart Citations
“…Reef-associated sharks have faced sharp declines in recent decades, especially in the Caribbean, with abundance negatively correlated to anthropogenic factors [ 1 4 ]. Recent analysis has found that abundance and species diversity of reef sharks was significantly lower in Belize, where shark fishing occurs, than in The Bahamas, where sharks are fully protected [ 5 ]. Despite the economic importance of reef shark species to several tourism-based economies [ 6 8 ] and fisheries [ 9 11 ], many species remain understudied in tropical seas, especially in low- and middle-income countries.…”
Section: Introductionmentioning
confidence: 99%